A negação no português falado em Vitória/ES - Nascimento, Cristiana Aparecida Reimann do (2014)
All languages have some way to express verbal denial, but each one has its own strategies for their achievement. In Brazilian Portuguese (BP), there are three strategies of denial: 1) preverbal (No+SV); 2) double denial (No+SV+No) and 3) postverbal (SV+No). In light of Variationist Sociolinguistics and based on the sample PortVix (Portuguese spoken in the City of Vitoria), which has as social parameters gender/sex of the speaker, their age and their level of education, this study examines the variation in the use of structures of denial in Portuguese spoken in the city of Vitoria/ES, in order to place, from this phenomenon, capixaba variety in Brazilian Portuguese. This study is also based upon the proposal of Schwenter (2005) that the three variants alternate only when denied content is activated in speech. Thus, if the proposition denied conveys a status of new information, just preverbal negation can be employed. Thereby, in our research, we seek to understand what factors influence the alternation of forms of denial and verify the linguistic-discursive contexts that bring this variation. When we compared our results with those of other studies, we found that double denial is quite productive in capixaba speech, representing 21.1 % of a total of 2263 data. When performing rounds in which two variants were amalgamated and opposed to one another, were selected by the program Goldvarb X (SANKOFF, TAGLIAMONTE and SMITH, 2005) and, therefore, considered statistically relevant to the double denial the following variables: the dialogical sequences, the absence of negative reinforcement, the absence of conversational markers and complete sentences. For postverbal negation, the following variables were selected: denied propositions directly activated and dialogical sequences. For pre-verbal negation, the statistically significant factors were: narrative and argumentative sequences, the presence of negative reinforcement, the presence of conversational markers, main clauses and male gender. The results revealed that the variation in the use of negative structures is essentially a discursive phenomenon, but this variation is also influenced by some syntactic factors.